Abortion and contraception for incarcerated people: A scoping review. - Martha Paynter; Paula Pinzón Hernández; Clare Heggie; Shelley McKibbon; Sarah Munro (PLoS ONE)
Background Women experiencing incarceration have higher rates of unmet contraceptive needs and rates of abortion than the public. Incarceration presents multiple potential barriers to accessing abortion and contraception care, including prison security protocols, prison locations, lack of access to care providers, stigma, and low health literacy. The objective of this scoping review is to understand the extent and type of evidence in relation to contraception and abortion access for people experiencing criminalization and incarceration. Methods We used the Joanna Briggs Institute methodology for scoping reviews and include empirical research with people experiencing criminalization or incarceration and/or with prison staff; with respect to prescription contraception or abortion access, while in custody or after having experienced incarceration/criminalization. Databases searched include CINAHL, APA PsycInfo, Gender Studies, Medline (Ovid), Embase, Sociological Abstracts, and Social Services Abstracts. The search yielded 6096 titles of which 43 were included in the review. Results Our search yielded 43 studies published between 2001 and 2021 across six countries. The studies included qualitative, quantitative, and mixed methods designs. The main outcomes of interest included contraceptive use; attitudes towards abortion, contraception, and pregnancy; and barriers to care. Barriers identified included lack of onsite access to options, contraceptive coercion by providers, financial costs, and disruptions to medical coverage and insurance status which incarcerated. Discussion Evidence indicates that people in prison face significant barriers to maintaining continuity of contraceptive methods, abortion access, and reproductive health guidance. Some studies articulated participants felt judged when discussing contraception with prison-based health care providers. Geographic location, out-of-pocket payments, and trust in health care providers were reported as barriers to access. Conclusion Incarceration presents considerable challenges to the access of contraception and abortion care. Future research should examine the interaction between institutional security policies and procedures on care seeking, the experiences of underserved and hyper-incarcerated groups, and the impact of being denied access to contraception and abortion and experiences of criminalization.